Determining Sincerity of Effort Based on Grip Strength Test in Three Wrist Positions - Petcharatana Bhuanantanondh; Pirun Nanta; Keerin Mekhora (Elsevier, 2018)
Background: Several grip strength tests are commonly used for detecting sincerity of effort. However, there is still no widely accepted standardized sincerity of effort test. Therefore, this study aimed to examine whether grip strength test in three wrist positions could distinguish between maximal and submaximal efforts. Methods: Twenty healthy individuals (10 men and 10 women) with a mean age of 26.7 ± 3.92 years participated in this study. All participants completed two test conditions (maximal and submaximal efforts) in three wrist positions (neutral, flexion, and extension) using both hands. Each participant exerted 100% effort in the maximal effort condition and 50% effort in the submaximal effort condition. The participants performed three repetitions of the grip strength test for each session. Results: The results showed that there is a significant main effect of the type of effort (p < 0.001), wrist position (p < 0.001), and hand (p = 0.028). There were also significant types of effort and wrist position interactions (p < 0.001) and effort and hand interactions (p < 0.028). The results also showed that grip strength was highest at the wrist in neutral position in both the maximal and the submaximal effort condition. Grip strength values of the three wrist positions in the maximal effort condition were noticeably greater than those in the submaximal effort condition. Conclusion: The findings of this study suggest that grip strength test in three wrist positions can differentiate a maximal effort from a submaximal effort. Thus, this test could potentially be used to detect sincerity of effort in clinical setting. Keywords: grip strength, maximal effort, sincerity of effort, submaximal effort, wrist position